Peranan Pengawasan Internal Dalam Rangka Mewujudkan Tata Kelola Pemerintahan Yang Baik: The Role of Internal Supervision in Order to Realize Good Governance - Segah, Boby (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
This paper aims to determine the factors that will affect the quality of the inspection results by the inspectorate of the Province and The Inspectorate of District / City to realize good and clean governance. Considering, in the implementation of internal supervisory examination, namely the Provincial Inspectorate and District/City Inspectorate in carrying out its duties supported by auditors who have passed the certification of visiting consisting of expert auditors, team level auditors and technical control auditors. Each audior has sufficient professional expertise and proficiency in carrying out inspection tasks that collectors in melakanakan must have the knowledge, expertise and experience required in carrying out the task. Work experience, independence, objectivity in conducting audits can provide opinions or conclusions as is without any influence from interested parties so that quality examination results can be achieved. The results of the study show that it is appropriate that the function of internal supervision is more empowered and implemented synergistically to achieve the goal of national and state or good governance in the public sector namely the realization of transparency, accountability, honesty, fairness and welfare of the community. With the supervision carried out in a tiered period of nausea from the SKPD interen to external examinations (BPK) then minimizing irregularities that occur in the next day inggat the importance of such supervision. From some of the experiences that occur then so much means supervision in tiers.